La persuasione nel discorso delle diete dimagranti — il caso della rivista femminile italiana Donna Moderna - Ozimska, Joanna (Neophilologica, 2019)
The paper analyzes the discourse of weight loss diets in a popular Italian magazine Donna Moderna. More than 230 examples were examined by means of rhetorical tools as a form of methodology, in particular basic kinds of appeals to persuade audience: Aristotle’s ethos, pathos and logos. The study sheds light on a significant role of topos of authority, additionally it lists and briefly characterizes dozens of other topoi (i.e., beauty, health, envy, fear, quantity, efficient cause). The discourse of diets never refers only to one topos at a time. The persuasion in this case is built up on different elements whose presence is mutually reinforced.